Pregnant Women in Louisiana Are Not Meeting Dietary Seafood Recommendations - M. L. Drewery; A. V. Gaitán; C. Thaxton; W. Xu; C. J. Lammi-Keefe (Hindawi Limited, 2016)
Background. The 2015-2020 Dietary Guidelines for Americans recommend that pregnant women and women of childbearing ages consume 8-12 oz. of seafood per week. Fish are the major dietary source of omega-3 long chain polyunsaturated fatty acids, which have benefits for the mother and fetus. Methods. In this observational study, we investigated dietary habits of pregnant women in Baton Rouge, Louisiana, USA, to determine if they achieve recommended seafood intake. A print survey, which included commonly consumed foods from protein sources (beef, chicken, pork, and fish), was completed by pregnant women at a single-day hospital convention for expecting families in October 2015. Women (n=221) chose from six predefined responses to answer how frequently they were consuming each food. Results. Chicken was consumed most frequently (75% of women), followed by beef (71%), pork (65%), and fish (22%), respectively. Consumption frequency for the most consumed fish (catfish, once per month) was similar to or lower than that of the least consumed beef, chicken, and pork foods. Consumption frequency for the most consumed chicken and beef foods was at least once per week. Conclusion. Our data indicate that pregnant women in Louisiana often consume protein sources other than fish and likely fail to meet dietary seafood recommendations.